Edematous myositis: a clinical presentation first suggesting dermatomyositis diagnosis. (15th June 2020) - Duchesne, Mathilde; Leonard‐Louis, Sarah; Landon‐Cardinal, Océane; Anquetil, Céline; Mariampillai, Kuberaka; Monzani, Quentin; Benveniste, Olivier; Allenbach, Yves
Abstract: Aims: Edema of the limbs is uncommon in idiopathic inflammatory myopathies (IIM). The few reported cases have been associated with severe and refractory dermatomyositis (DM), sometimes in association with cancers. We aimed to determine if edematous myositis is a homogeneous subtype based on clinical, serological and pathological features. Methods: This is a retrospective observational study performed between 2008 and 2015 in the French national referral center for myositis. All adult patients with an inflammatory muscle biopsy and upper limbs edema were included as well as IIM cases without limb edema as controls. Clinical, biological and pathological features were collected. Results: Seventeen edematous myositis were included and compared to 174 IIM without edema, including 50 DM controls. Edema was the first manifestation in 23% of patients. Muscle weakness was severe and symmetric, 71% of patients presented dysphagia and a restrictive ventilatory pattern was found in 40%. Fifty‐two percent of patients had a typical DM skin rash and 23% had cancer within 3 years of diagnosing myositis. Fifty‐three percent of patients presented a myositis specific antibody and only DM‐specific antibodies were detected. Classic pathological DM features (perifascicular atrophy, perifascicular/perimysial perivascular inflammation) were uncommon but capillary C5b‐9 deposition and MxA expression were seen in 79% and 73% of cases, respectively. A perimysial edema was found in 82% of cases. Seventeen percent of patients died (median follow up of 18 months). Edematous myositis demonstrated more marked capillary C5b‐9 deposition compared to IIM controls. There was no clinical, biological or pathological difference with DM controls except for limb edema. Conclusion: Our study underlines that limb edema could be a symptom of IIM and that edematous myositis are mostly DM. The vasculopathy seems to play a key role in its pathophysiology. Limb edema associated with muscle impairment should suggest the diagnosis of DM in clinical settings.